الوقف والابتداء في القرآن الكريم والاستفادة منهما في تعليم اللغة العربيةفي سورة الشورى نموذجا - SAAD IDRIS; MULYADI (Rayah Al-Islam, 2018)
Surely Arabic language has a very high degree in Islam, in which the last holy book was revealed, and that’s Alqur’an. It is also the language of Islamic society and civilization whose authenticity will endlessly be protected until the judgement day, since Alloh guaranteed its authenticity as he said in surah Al hijr : 9 ) “ indeed, it is We who sent down the Qur’an and indeed, We will be its guardian” because of its very high degree, the muslim scholars encourage all muslims to learn and teach this language. Mastering Arabic language requires complete understanding of Arabic grammars, two of which are “alwaqf” and “Al Ibtida’I”. They are one of the important grammars that help readers of Qur’an, teachers and students to understand the meaning of Qur’anic Verses correctly so that they make no mistake or problem that might lead to false meaning when reading or speaking about Quranic Verses. In this topic researcher used an analytical descriptive approach, that is to find information related to the topic to gain the result, analyze it and lastly implement it in the teaching of Arabic language.This research proved that Waqf, a study which studies about how to cut reading intended to avoid any fallacy of meaning among Quranic Verses, and Al-Ibtida, a study that studies how to begin a reading intended to complete the meaning of Qur'anic verses, And that the Waqf and Al ibtida’ is divided into four sections namely Tam, Kaf, Hassan, and qobih, and can be used in the field of teaching the Arabic language, by putting them in the sentences useful and in the texts of reading and dialogue, and then the teacher to explain the positions of stop and start in the sentences useful in view of grammatical provisions.